Drought limitations to leaf‐level gas exchange: results from a model linking stomatal optimization and cohesion–tension theory. (8th January 2016) - Novick, Kimberly A.; Miniat, Chelcy F.; Vose, James M.
Abstract: We merge concepts from stomatal optimization theory and cohesion–tension theory to examine the dynamics of three mechanisms that are potentially limiting to leaf‐level gas exchange in trees during drought: (1) a 'demand limitation' driven by an assumption of optimal stomatal functioning; (2) 'hydraulic limitation' of water movement from the roots to the leaves; and (3) 'non‐stomatal' limitations imposed by declining leaf water status within the leaf. Model results suggest that species‐specific 'economics' of stomatal behaviour may play an important role in differentiating species along the continuum of isohydric to anisohydric behaviour; specifically, we show that non‐stomatal and demand limitations may reduce stomatal conductance and increase leaf water potential, promoting wide safety margins characteristic of isohydric species. We used model results to develop a diagnostic framework to identify the most likely limiting mechanism to stomatal functioning during drought and showed that many of those features were commonly observed in field observations of tree water use dynamics. Direct comparisons of modelled and measured stomatal conductance further indicated that non‐stomatal and demand limitations reproduced observed patterns of tree water use well for an isohydric species but that a hydraulic limitation likely applies in the case of an anisohydric species. Abstract : This work represents a novel merging of concepts from stomatal optimization theory and cohesion–tension theory to examine the mechanisms that are potentially limiting to leaf gas exchange during drought. The model is used to identify distinguishing characteristics of 'demand limitations' to gas exchange imposed by atmospheric vapour pressure deficit, 'hydraulic limitations' to gas exchange imposed by the plant's need to prevent excessive cavitation and 'non‐stomatal limitations' to gas exchange imposed by declining leaf water status. We demonstrate that these features are frequently detected in observations of tree water use and that demand and non‐stomatal limitations may reduce stomatal conductance and increase leaf water potential, promoting wide safety margins characteristic of isohydric species. The coherent mapping of the model predictions to the empirical observations described in this study is encouraging and can inform and motivate ongoing efforts to explore how these different mechanisms jointly or independently regulate leaf‐level gas exchange during drought.